A Study to Assess the Efficacy of Audio-Visual Psychoeducation on Level of Knowledge and Attitude Regarding Harmful Effects of Alcohol among Alcohol use Disorder Patients Admitted to Mental Health Units of Selected Hospitals of Western Maharashtra - Seema Madhavan Nair; Punita A Sharma; Radhika Das (Indian Journal of Psychiatric Nursing)
Introduction: Alcohol use disorder (AUD) has emerged as a global concern in the world, due to its harmful impact on health, social, economic, and legal aspects. Several established treatment approaches, both pharmacological and nonpharmacological are available but have only modest success. Relapse in alcohol use is noted to be common following treatment, hence efficacy of newer modalities of treatment or therapies is needed. Aim: This study aims to assess the efficacy of audiovisual psychoeducation on the level of knowledge and attitude of harmful effects of alcohol among AUD patients admitted to mental health units of selected hospitals of Western Maharashtra. Materials and Methodology: A quantitative research approach with pretest-posttest control design was adopted in the study. The sample size was estimated to be 70 based on the pilot study and settings were mental health units of selected hospitals in Western Maharashtra. A simple random sampling technique was used with random allocation of subjects into experimental group and control group by lottery method. A structured tool to assess knowledge was developed, validated by experts and reliability was tested. Alcohol Decisional Balance Scale, which is a standardized tool was used for assessing the attitude. Pretest knowledge assessment was done for control and experimental groups. Audiovisual psychoeducation was given to the experimental group. Both the groups were receiving routine care. A posttest assessment was done after 7 days of intervention. Results: Findings revealed that there is statistically significant increase in the level of knowledge from pretest mean score of 9.37 + 3.191–14.06 + 4.179 in posttest of the experimental group by Wilcoxon Z value test at the level of significance P < 0.0001 showing the efficacy of audio-visual psychoeducation in changing the level of knowledge. Similarly, postintervention attitude distribution assessment in the experimental group revealed a statistically significant difference in positive attitude from 6 (17%) in pretest to 12 (34%) in posttest with the McNemar's test at level of significance of P < 0.031. Correlation in level of knowledge with attitude revealed a weak positive correlation with r = 0.17. There was no significant association of pretest knowledge with selected socio-demographic data. Conclusion: Audiovisual psychoeducation is efficient in increasing the level of knowledge and change in attitude toward harmful effects of alcohol.